EMPTY BOX AS SYMBOLIC ACTION: YOUNG VOTERS’ REJECTION OF THE SOLE CANDIDATE IN GRESIK’S LOCAL - Erfina Dwi; Agus Machfud Fauzi; Rizky Trisna Putri (Politik Indonesia: Indonesian Political Science Review, 2025)
This study explores the symbolic meaning behind the choice of the "empty box" (kotak kosong) among young voters in the 2024 regional election (Pilkada) in Gresik, where only one candidate was on the ballot. Rather than seeing this choice as political apathy, this research interprets it as a conscious act of resistance and a demand for genuine political representation. Using a qualitative descriptive approach and symbolic interactionism theory, the study examines how young voters construct political meaning through their decision to vote for the empty box. Data were collected through in-depth interviews with informants aged 17–25 who reside in Gresik and intentionally voted for the empty box. The findings reveal that their decisions were shaped by critical reflection, peer discourse, and disillusionment with the lack of electoral competition. The act of selecting the empty box is understood as a symbolic expression of frustration, political identity, and expectations for democratic renewal. This study contributes by offering an empirical explanation of how symbolic political choices function as a form of youth resistance, a dimension rarely discussed in previous research on uncontested elections in Indonesia. It also provides a nuanced interpretation of the empty-box vote as a meaning-making process rather than a mere protest action.